2015
DOI: 10.1021/cb500757u
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Library Approach to Uncover Phosphomimetic Inhibitors of the BRCA1 C-Terminal Domain

Abstract: Many intracellular protein–protein interactions are mediated by the phosphorylation of serine, and phosphoserine-containing peptides can inhibit these interactions. However, hydrolysis of the phosphate by phosphatases, and the poor cell permeability associated with phosphorylated peptides has limited their utility in cellular and in vivo contexts. Compounding the problem, strategies to replace phosphoserine in peptide inhibitors with easily accessible mimetics (such as Glu or Asp) routinely fail. Here, we pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 62 publications
0
39
0
Order By: Relevance
“…Thiol bis-alkylation has also been applied to mRNA display libraries (Schlippe, Hartman, Josephson, & Szostak, 2012). In one such selection, all the selected peptides were cyclic, even those containing a single cysteine; the mxy linker unexpectedly formed a small ring with the N-terminal methionine (White et al, 2015). The rapid cross-linking of cysteine and methionine using dibromoxylene linkers is an observation that we have confirmed in our lab (see later).…”
Section: Using Thiol Alkylation To Constrain Peptidesmentioning
confidence: 99%
“…Thiol bis-alkylation has also been applied to mRNA display libraries (Schlippe, Hartman, Josephson, & Szostak, 2012). In one such selection, all the selected peptides were cyclic, even those containing a single cysteine; the mxy linker unexpectedly formed a small ring with the N-terminal methionine (White et al, 2015). The rapid cross-linking of cysteine and methionine using dibromoxylene linkers is an observation that we have confirmed in our lab (see later).…”
Section: Using Thiol Alkylation To Constrain Peptidesmentioning
confidence: 99%
“…The dibromoxylene cyclization chemistry has already been shown to be compatible with mRNA display. 56, 57, 58 However, others have shown that CuAAC reagents degrade nucleic acids over time and that RNA is particularly susceptible to oxidation. 59, 60 The use of polytriazole ligands, such as tris[(1-benzyl-1H-1,2,3-triazol-4-yl)methyl]amine (TBTA) or the water-soluble tris(3-hydroxypropyl-triazolylmethyl)amine (THPTA), have been shown to protect Cu(I) from oxidation or disproportionation.…”
Section: Resultsmentioning
confidence: 99%
“…56, 57 We designed five libraries, each containing two cysteine codons (one fixed at the 3′ end of the random region and one that was varied), and one Phe codon that was varied in position between libraries (Figure 4a–c and Supporting Figure S6). The initiator Met codon fixed the position of the azide to the N-terminus.…”
Section: Resultsmentioning
confidence: 99%
“…Natarajan and co‐workers later identified a difluorophosphonate‐containing compound with K d 0.71 μ m. White et al. developed a non‐phosphorylated peptide inhibitor Peptide 8.6 ( K d 3.6 μ m ) with glutamic acid as a pSer mimic, using mRNA display technology. The peptidic nature and/or charge of these inhibitors limits their further development for use in chemical biology or therapy.…”
Section: Introductionmentioning
confidence: 99%